Tanggungjawab Pihak Pengembang Perumahan Berdasarkan Perjanjian Jual Beli dengan Konsumen di Kota Pekanbaru - Frans Mitrano (Jurnal Hukum Respublica, 2020)
Housing is a group of houses that function as a residential area equipped with environmental infrastructure, namely the basic physical features of the environment, for example the provision of drinking water, garbage disposal, availability of electricity, telephone, roads, which enable the residential environment to function properly. Home is a place to let go of fatigue, a place to hang out, and foster a sense of kinship among family members, a place for family shelter and to store valuables. A house is a physical structure consisting of a room, yard and surrounding area which is used as a place to live and a means of family formation. According to WHO (World Health Organization), a house is a physical structure or a building for shelter, where the environment is useful for physical and spiritual health and social conditions, both for family and individual health. The main issue is what is the responsibility of the housing developer based on the sale and purchase agreement with consumers in the city of Pekanbaru and what are the legal consequences of the responsibility of the housing developer based on the sale and purchase agreement with consumers in the city of Pekanbaru. As for this research is a sociological legal research, so this research is descriptive analysis Abstract